Sweet potato chips and flakes - Rosal, Mildred A.; Guzman, Matilde, P. (1968.)
The sweet potato products, chips and flakes, were prepared employing methods patterned after potato chip processing and flake processing. Tests consisted of moisture and sugar determinations, peroxidase test, % fat content, tenderness test and subjective evaluation. Results of the subjective tests showed better quality of the flakes and a marked preference for them over the chips.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Sweet potato chips